A vital sign monitoring device - Goh, Geng Ting (2019)
Vital signs can be detected such as heart rate that is an important indicator that needs to be monitored so that any abnormality can be detected early enough for prevention. We would be in serious trouble without a heartbeat, so pulse or heart rate is by far the most important parameter to be monitored. The aim of this project is to design and compute the data to test the reliability of a heart monitor device that continuously monitors the heart rate, as compared to OMRON which is certified in the market. OMRON is a leading healthcare products provider in the market for blood pressure monitors. In addition, regression method is used to test out the accuracy of the heart rate monitor device to OMRON. The study of ECG is crucial too and it is used to compare it with the heart rate monitor device. The software development of the project is used through the implementation of Arduino and analyzes it with the regression method in WEKA.